Autoinducer-2 Facilitates Pseudomonas aeruginosa PAO1 Pathogenicity in Vitro and in Vivo - Li, Hongdong; Li, Xingyuan; Song, Chao; Zhang, Yunhui; Wang, Zhengli; Liu, Zhenqiu; Wei, Hong; Yu, Jialin (Frontiers in Microbiology, 2017)
Bacterial communication systems, such as quorum sensing (QS), have provided new insights of alternative approaches in antimicrobial treatment. We recently reported that one QS signal, named as autoinducer-2 (AI-2), can affect the behaviors of Pseudomonas aeruginosa PAO1 in a dose-dependent manner. In this study, we aimed to investigate the effects of AI-2 on P. aeruginosa PAO1 biofilm formation and virulence factors production in vitro, and in vivo using a pulmonary infection mouse model. Exogenous AI-2 resulted in increased biofilms architecture, the number of viable cells, and the yield of pyocyanin and elastase virulence factors in wild type P. aeruginosa PAO1. However, no such effect was observed in P. aeruginosa lasR rhlR mutant strain. In vivo, the use of AI-2 significantly increased the mortality, lung bacterial count and histological lung damage of mice with acute P. aeruginosa PAO1 infection. Our data suggest that AI-2 promotes the formation of P. aeruginosa PAO1 biofilms and the production of virulence factors by interfering with P. aeruginosa QS systems, resulting in decreased host survival. AI-2 may be a therapeutic target for the clinical treatment of a co-infection of P. aeruginosa and AI-2 producing bacteria.